Comparison of apical periodontitis repair in endodontic treatment with calcium hydroxide-dressing and aPDT - Lea Assed Bezerra da SILVA; Zobélia Maria de Souza LOPES; Rafaela Cardoso de SÁ; Arthur Belém NOVAES JÚNIOR; Priscilla Coutinho ROMUALDO; Marília Pacífico LUCISANO; Paulo NELSON-FILHO; Raquel Assed Bezerra da SILVA
Abstract This study evaluated the effect of antimicrobial photodynamic therapy (aPDT) on the endodontic treatment of apical periodontitis (AP). AP was induced in 48 premolars of 6 dogs. After biomechanical preparation, the teeth were divided into 4 groups: Calcium-Hydroxide (CH)/120d and CH/180d: root canals filled with CH-based dressing for 15 days before obturation; aPDT/120d and aPDT/180d: conditioning with phenothiazine photosensitizer (10 mg/mL) for 1 minute and irradiation with diode laser in the same session as obturation. Root filling was performed with AH Plus sealer. After the experimental periods, animals were euthanized and teeth were submitted for histology. HE staining was performed for descriptive analysis of the periapical region, measurement of apical periodontitis and for inflammatory cells, and blood vessels count. Immunohistochemistry was performed for osteopontin (OPN) and alkaline phosphatase (ALP). Data were analyzed statistically by two-way ANOVA and chi-square test (α = 5%). Teeth in Group CH/120d presented only a slightly enlarged periodontal ligament (PL) with advanced repair. Group aPDT/120d presented the PL moderately enlarged, with moderate inflammatory infiltrate and few collagen fibers. The same pattern was observed at 180 days. AP lesions in CH-treated groups were smaller than those in aPDT-treated groups (p < 0.001) with more blood vessels (p < 0.0001), regardless of the evaluation period, without significant differences in the number of inflammatory cells (p > 0.05). CH-treated groups showed significantly more intense immunostaining for ALP and OPN (p < 0.001) in both periods. Although aPDT stimulated angiogenesis and expression of bone formation markers, the two-session endodontic treatment with CH-based dressing promoted better apical periodontitis repair.